A Rich Coolie Merchant Wife, Trinidad, B.W.I. - (:unkn) unknown (My University, 2008)
This portrait of a married East Indian woman was taken in a photographic studio circa 1900.
Colour: Black and White; Style: Portrait; Other: Bordered, Undivided
Keywords: Postcards; Women, East Indian--Trinidad and Tobago; Ethnic costume--India; Married women--Trinidad and Tobago; Wives--Trinidad and Tobago; Skirts--India; Bodices--India; Nose rings--India; Necklaces--India; Armbands--India; Bracelets--India; Jewelry--India; Hair ornaments--India; Women's clothing--India; Saris--India; East Indians--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Merchants--Trinidad and Tobago; Businesspeople--Trinidad and Tobago; Women--Trinidad and Tobago; [1900]